Psychoeducational Interventions for Problematic Anger in Chronic Moderate to Severe Traumatic Brain Injury: A Study of Treatment Enactment. (January 2020) - Hart, Tessa; Vaccaro, Monica J.; Fann, Jesse R.; Maiuro, Roland D.; Neuberger, Shira; Sinfield, Steven
Abstract: Objectives: Treatment enactment, a final stage of treatment implementation, refers to patients' application of skills and concepts from treatment sessions into everyday life situations. We examined treatment enactment in a two-arm, multicenter trial comparing two psychoeducational treatments for persons with chronic moderate to severe traumatic brain injury and problematic anger. Methods: Seventy-one of 90 participants from the parent trial underwent a telephone enactment interview at least 2 months (median 97 days, range 64–586 days) after cessation of treatment. Enactment, quantified as average frequency of use across seven core treatment components, was compared across treatment arms: anger self-management training (ASMT) and personal readjustment and education (PRE), a structurally equivalent control. Components were also rated for helpfulness when used. Predictors of, and barriers to, enactment were explored. Results: More than 80% of participants reported remembering all seven treatment components when queried using a recognition format. Enactment was equivalent across treatments. Most used/most helpful components concerned normalizing anger and general anger management strategies (ASMT), and normalizing traumatic brain injury-related changes while providing hope for improvement (PRE). Higher baseline executive function and IQ were predictive of better enactment, as well as better episodic memory (trend). Poor memory was cited by many participants as a barrier to enactment, as was the reaction of other people to attempted use of strategies. Conclusions: Treatment enactment is a neglected component of implementation in neuropsychological clinical trials, but is important both to measure and to help participants achieve sustained carryover of core treatment ingredients and learned material to everyday life.